Soil CO2 emission and soil attributes associated with the microbiota of a sugarcane area in southern Brazil - Mara Regina Moitinho; Daniel De Bortoli Teixeira; Elton da Silva Bicalho; Alan Rodrigo Panosso; Antonio Sergio Ferraudo; Gener Tadeu Pereira; Siu Mui Tsai; Beatriz Maria Ferrari Borges; Newton La Scala Jr. (Scientific Reports, 2021)
Abstract The spatial structure of soil CO2 emission (FCO2) and soil attributes are affected by different factors in a highly complex way. In this context, this study aimed to characterize the spatial variability patterns of FCO2 and soil physical, chemical, and microbiological attributes in a sugarcane field area after reform activities. The study was conducted in an Oxisol with the measurement of FCO2, soil temperature (Ts), and soil moisture (Ms) in a regular 90 × 90-m grid with 100 sampling points. Soil samples were collected at each sampling point at a depth of 0–0.20 m to determine soil physical (density, macroporosity, and microporosity), particle size (sand, silt, and clay), and chemical attributes (soil organic matter, pH, P, K, Ca, Mg, Al, H + Al, cation exchange capacity, and base saturation). Geostatistical analyses were performed to assess the spatial variability and map soil attributes. Two regions (R1 and R2) with contrasting emission values were identified after mapping FCO2. The abundance of bacterial 16S rRNA, pmoA, and nifH genes, determined by real-time quantitative PCR (qPCR), enzymatic activity (dehydrogenase, urease, cellulase, and amylase), and microbial biomass carbon were determined in R1 and R2. The mean values of FCO2 (2.91 µmol m−2 s−1), Ts (22.6 °C), and Ms (16.9%) over the 28-day period were similar to those observed in studies also conducted under Oxisols in sugarcane areas and conventional soil tillage. The spatial pattern of FCO2 was similar to that of macropores, air-filled pore space, silt content, soil organic matter, and soil carbon decay constant. No significant difference was observed between R1 and R2 for the copy number of bacterial 16S rRNA and nifH genes, but the results of qPCR for the pmoA gene presented differences (p < 0.01) between regions. The region R1, with the highest FCO2 (2.9 to 4.2 µmol m−2 s−1), showed higher enzymatic activity of dehydrogenase (33.02 µg TPF g−1 dry soil 24 h−1), urease (41.15 µg NH4–N g−1 dry soil 3 h−1), amylase (73.84 µg glucose g−1 dry soil 24 h−1), and microbial biomass carbon (41.35 µg C g−1 soil) than R2, which had the lowest emission (1.9 to 2.7 µmol m−2 s−1). In addition, the soil C/N ratio was higher in R2 (15.43) than in R1 (12.18). The spatial pattern of FCO2 in R1 and R2 may not be directly related to the total amount of the microbial community (bacterial 16S rRNA) in the soil but to the specific function that these microorganisms play regarding soil carbon degradation (pmoA).